A HISTORY OF DIGITAL MARKETING - Kurolov Maksud Obitovich (Scholar Express Journals, 2022)
The current paper delves into historical properties of Digital Marketing an d Marketing Strategy. The study of Digital marketing is essential especiall y for companies who intend to increase their outcome by applying the hi storical approaches to their management strategy. The paper is intended to help organizations to improve their effectiveness by promoting internall y amid their members, the development of the capacity to generate inno vative ideas.
Keywords: Marketing; strategy; digital marketing; marketing